Narrative approach to the problem of identity in analytical philosophy (Actual Problems of Mind, 2020)
Abstract. The article considers the narrative approach to the problem of personal identity in analytic philosophy. It states that the narrative approach develops, together with the normative one, as opposed to the metaphysical view on identity. The article admits that the normative and narrative approaches are similar to each other, as they both consider personal identity as a category based on the values. Moreover, they both regard a person as an agent, conscious of their actions. Nevertheless, the narrative approach differs from the normative. The narrative approach deepens the understanding of a person as an agent, adding that a person is not only conscious of the actions and can attribute them to the self but also articulates being an agent. All experience gained by a person unites into a single succession of events – the narrative. Thus, it is not only an autobiographical story but also the way of a person being over time. The article reveals the main features of the narrative: plausibility, teleology, thematic connectedness between events, flexibility, dynamism, and its social nature. It states that personal identity is the unity of a person's self over time. So this category is treated as based on practical principles. Creating an autobiographical story, a person realizes themselves as a unique being, who remains the same over time. The narrative appears as the condition of personal identity. The article characterizes the procedure of re-identification or characterization as a mechanism of keeping identity over time. Gaining a new piece of experience, a person synthesizes it with the previous one. In such a way, personal identity reproduces and keeps over time. Since a person can create and maintain the unity of the self only in the narrative, the latter is the only criterion of identity. The paper also considers the critical remarks put forward to the narrative approach by J. Davenport, E. Rudd, G. Strawson, and D. Shoemaker. All arguments, introduced against the narrative approach, can be reduced to following: ontological, epistemological and practical. The final part of the article outlines them.
Keywords: identity, person, agent, narrative, re-identification.